2020
DOI: 10.1111/ahe.12609
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations in cervical vertebrae in two species of neotropical canids: What is the meaning?

Abstract: Anatomical variation in wild canids is rarely described. Altered shapes, uni‐ or bilaterally situated, were observed in ventral laminae of C6 and/or in C7 vertebral body of two fox species: Lycalopex gymnocercus and Cerdocyon thous. The specimens were young adults, collected dead on highways in southern Brazil. Deformities were considered anatomical variations because apparently there was no interference in function. The occurrence of such variations in two related species from the same area can suggest an env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Interestingly, in a study of wild foxes in Brazil, malformations of the ventral lamina on C6 and C7 were found to be similar in shape to those described in [19]. In another study, similar cervical vertebral malformations in a highly inbred wolf population on a remote island were detected and interpreted to be intersegmental transitional vertebrae [20].…”
Section: Introductionmentioning
confidence: 69%
“…Interestingly, in a study of wild foxes in Brazil, malformations of the ventral lamina on C6 and C7 were found to be similar in shape to those described in [19]. In another study, similar cervical vertebral malformations in a highly inbred wolf population on a remote island were detected and interpreted to be intersegmental transitional vertebrae [20].…”
Section: Introductionmentioning
confidence: 69%
“…Kürtül et al 16 evaluated 116 SA in German shepherd dogs; in all cases, the VA was the first branch of SA and entered the transverse foramen of C6. Asymptomatic, uni-or bilaterally altered ventral laminae of C6 and/or an anomaly of C7 were observed on the vertebral body of two wild fox species 17 and thoroughbred horses. 18 The morphological variations of the vascular tree were not focused in these studies.…”
Section: Learning Points/take-home Messagesmentioning
confidence: 99%